2003
DOI: 10.1016/s0377-1237(03)80144-2
|View full text |Cite
|
Sign up to set email alerts
|

Nuss Procedure for Pectus Excavatum – An early Experience

Abstract: The technique of minimally invasive repair of pectus excavatum is a new operation that allows for repair of this deformity without any cartilage resection or sternal osteotomy. The procedure has revolutionized the management of pectus excavatum. Six cases of pectus excavatum were referred to our centre for surgical correction. However, based on Haller's CT index 2 merited surgery. Our results suggest that the minimally invasive repair of pectus excavatum is an exciting operation with minimal morbidity and exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Then the centerline is projected to the costal surface fitted by the ribs and cartilages using thin plate spline [15]. The correction device is estimated based on the projected centerline with the typical pectus bar size of 1.5cm width and 2 mm thickness [16]. The estimated correction device is personalized to PE patient's costal curvature instead of their skin profile, which is more precise and accurate especially for female patients.…”
Section: Correction and Estimation Of Correction Device Del Buildingmentioning
confidence: 99%
“…Then the centerline is projected to the costal surface fitted by the ribs and cartilages using thin plate spline [15]. The correction device is estimated based on the projected centerline with the typical pectus bar size of 1.5cm width and 2 mm thickness [16]. The estimated correction device is personalized to PE patient's costal curvature instead of their skin profile, which is more precise and accurate especially for female patients.…”
Section: Correction and Estimation Of Correction Device Del Buildingmentioning
confidence: 99%
“…We have been performing a rather modified version of the Nuss procedure for pectus excavatum in India since 2012 using video-endoscope, pectus tunneloscopy along with various fixation devices and our described sutureless moon bridge system for a stable bar [2,3]. A few reports on Nuss procedure for pectus excavatum from India can be traced back to Puri et al who reported 2 cases in pediatric age group in 2003 [4]. In view of the relatively normal cardio-respiratory function, the main concern in people with this deformity is about a good cosmetic correction, which will enable them to do outdoor activities, as well as alleviate their psychological problems and thus improve the quality of their life.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence and etiology of chest wall deformities, among the Indian population still remain unexplained and only scanty literature was retrieved on extensive search from [7] the journal web , probably pointing towards the lack of objective documentation about the deformity. Pectus that correction is necessary .…”
Section: Introductionmentioning
confidence: 99%